2018
DOI: 10.1016/j.gca.2018.03.022
|View full text |Cite
|
Sign up to set email alerts
|

Chlorine isotopic compositions of apatite in Apollo 14 rocks: Evidence for widespread vapor-phase metasomatism on the lunar nearside ∼4 billion years ago

Abstract: Compared to most other planetary materials in the Solar System, some lunar rocks display high δ 37 Cl signatures. Loss of Cl in a H< Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
37
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 93 publications
(122 reference statements)
3
37
0
1
Order By: Relevance
“…; Potts et al. ). Isotopic fractionation from degassing assuming Graham's Law diffusion and Rayleigh Distillation can be modeled such thatδnormalFinal=δnormalInitial+false(1000+δInitialfalse)×F(α1)normalRemaining1whereα=M1M2and M 1 is the mass of the light isotopologue (i.e., Fe 35 Cl 2 ), and M 2 is the mass of the heavy isotopologue (i.e., Fe 35 Cl 37 Cl).…”
Section: Differentiated Bodies—earth Mars and Moonmentioning
confidence: 98%
See 1 more Smart Citation
“…; Potts et al. ). Isotopic fractionation from degassing assuming Graham's Law diffusion and Rayleigh Distillation can be modeled such thatδnormalFinal=δnormalInitial+false(1000+δInitialfalse)×F(α1)normalRemaining1whereα=M1M2and M 1 is the mass of the light isotopologue (i.e., Fe 35 Cl 2 ), and M 2 is the mass of the heavy isotopologue (i.e., Fe 35 Cl 37 Cl).…”
Section: Differentiated Bodies—earth Mars and Moonmentioning
confidence: 98%
“…If devolatilization occurred, the d 37 Cl values could be raised from a nebular value of À7& to a near-zero value seen on Earth. Chlorine degassing has been shown to produce significant heavy isotope enrichments resulting in high d 37 Cl values >35& measured in lunar samples (Sharp et al 2010b;Boyce et al 2015;Barnes et al 2016;Potts et al 2018). Isotopic fractionation from degassing assuming Graham's Law diffusion and Rayleigh Distillation can be modeled such that Fig.…”
Section: Chlorine Devolatilization During Planet Formationmentioning
confidence: 99%
“…The formation of perchlorate fractionates Cl isotopes [39,45], but only a few examples of extreme δ 37 Cl values have been found on Earth, e.g., 12% in volcanic fumaroles [46]. This behavior is in contrast to lunar samples, where δ 37 Cl values as high as 81.1% have been reported [36,37], which is possibly due to the large kinetic isotope effects during the rapid diffusion of chlorine species to the vapor phase during degassing [41]. Kusebauch et al [47] suggested that fluid-rock interactions may not only cause elemental mobilization but in some cases also the fractionation of their isotopes.…”
Section: Introductionmentioning
confidence: 97%
“…The ratio of two stable isotopes 37 Cl and 35 Cl in an unknown sample is usually compared to standard mean ocean chloride (SMOC) using Equation (1) δ 37 Cl =       37 Cl/ 35 Cl sample 37 Cl/ 35 Cl SMOC − 1       × 1000 (1) and is reported in the standard per mil notation (% ). Chlorine isotopes have recently gained attention in studies of lunar [32][33][34][35][36][37] and Martian apatite samples [38,39]. In lunar materials, relatively large natural variations in δ 37 Cl have been detected (from −1% up to 40% [32,36] or even from 3.8% to 81.1% [37]), while the range of δ 37 Cl in terrestrial geological samples is much smaller with the vast majority of values falling between −2% and 2% [40,41].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation